La consulta previa en actividades extractivas: un análisis del balance y propuestas a 10 años de su aplicación en el Perú - O’Diana Rocca, Richard (2022)
Prior consultation is one of the most important instruments for the relationship between the State and the indigenous peoples. Prior consultation is also a key right for the survival and respect for the ways of life of indigenous peoples. This right is included in ILO Convention 169 and calls on the State Party to sit down face to face with indigenous peoples before issuing an administrative or legislative measure that may affect them.However, prior consultation is not only a right, but also an administrative procedure. It is there where the procedure has presented several improvable and perfectible factors. In the following article, we will analyze a series of elements of the prior consultation processes that need to be improved, focusing on the field of extractive activities.